Undergraduate Medical Students' Usage and Perceptions of Anatomical Case‐Based Learning: Comparison of Facilitated Small Group Discussions and eLearning Resources. Issue 3 (30th October 2018) - Holland, Jane C.; Pawlikowska, Teresa
Abstract: While case‐based discussions can empower students to apply knowledge to contextual clinical situations, scheduling these activities is a challenge in crowded curricula. Case‐based eLearning activities, derived from existing cases discussed within anatomy small group tutorials, were created incorporating principles such as interactivity, reinforcement, and feedback. Over half of the students accessed one or more of these online cases, with 18% accessing all eight online cases provided. Access increased as the semester progressed, particularly just before summative examinations, implying students used these primarily as revision aides. Students rated both formats highly, but favored the online format with regard to enjoyment ( P = 0.048), learning ( P = 0.101), and feedback ( P = 0.086). However, more students discussed these cases in small group tutorials within the anatomy dissecting room than completed them online (122 vs. 67) and themes emerging from free text comments included a desire to have more time dedicated to these cases during small group tutorials, and an appreciation for the opportunity for discussion with staff and learning through doing . Additionally, native English speakers rated the anatomy room discussions significantly higher in all aspects than non‐native English speakers, suggesting that non‐native speakers may be hesitant or reluctant to fully participate in front of peers. While online case‐based learning activities are a useful adjunct to anatomy teaching, particularly for revision, assumptions that " digital natives " have an innate preference for digital resources require critical evaluation, as students still place a high value on opportunities for discussion with staff during their studies.